Distinct Chemotaxis Protein Paralogs Assemble into Chemoreceptor Signaling Arrays To Coordinate Signaling Output - Lindsey O’Neal (American Society for Microbiology, 2019)
ABSTRACT Most chemotactic motile bacteria possess multiple chemotaxis signaling systems, the functions of which are not well characterized. Chemotaxis signaling is initiated by chemoreceptors that assemble as large arrays, together with chemotaxis coupling proteins (CheW) and histidine kinase proteins (CheA), which form a baseplate with the cytoplasmic tips of receptors. These cell pole-localized arrays mediate sensing, signaling, and signal amplification during chemotaxis responses. Membrane-bound chemoreceptors with different cytoplasmic domain lengths segregate into distinct arrays. Here, we show that a bacterium, Azospirillum brasilense, which utilizes two chemotaxis signaling systems controlling distinct motility parameters, coordinates its chemotactic responses through the production of two separate membrane-bound chemoreceptor arrays by mixing paralogs within chemotaxis baseplates. The polar localization of chemoreceptors of different length classes is maintained in strains that had baseplate signaling proteins from either chemotaxis system but was lost when both systems were deleted. Chemotaxis proteins (CheA and CheW) from each of the chemotaxis signaling systems (Che1 and Che4) could physically interact with one another, and chemoreceptors from both classes present in A. brasilense could interact with Che1 and Che4 proteins. The assembly of paralogs from distinct chemotaxis pathways into baseplates provides a straightforward mechanism for coordinating signaling from distinct pathways, which we predict is not unique to this system given the propensity of chemotaxis systems for horizontal gene transfer. IMPORTANCE The assembly of chemotaxis receptors and signaling proteins into polar arrays is universal in motile chemotactic bacteria. Comparative genome analyses indicate that most motile bacteria possess multiple chemotaxis signaling systems, and experimental evidence suggests that signaling from distinct chemotaxis systems is integrated. Here, we identify one such mechanism. We show that paralogs from two chemotaxis systems assemble together into chemoreceptor arrays, forming baseplates comprised of proteins from both chemotaxis systems. These mixed arrays provide a straightforward mechanism for signal integration and coordinated response output from distinct chemotaxis systems. Given that most chemotactic bacteria encode multiple chemotaxis systems and the propensity for these systems to be laterally transferred, this mechanism may be common to ensure chemotaxis signal integration occurs.